Vaccinoprophylaxis of Hepatitis B N.A - N. A. Ozeretskovsky; N. V. Shalunova; E. M. Petruchuk; I. N. Indikova (Эпидемиология и вакцинопрофилактика)
The review summarizes the WHO materials and recommendations the latest editions of the official guidelines of the Ministries of Health Australia, Canada, Great Britain, Germany, Russia, USA, through the vaccination of viral hepatitis B. Special attention is paid to the immunization of persons belonging to the group of increased risk of the infection, the implementation of which is not fully defined in relation to native normative documents: the immunocompromise, hemodialyse, diabetic patients and healthscare personel.